National Culture Moderates Corporate Governance and Integrated Reporting - Machmuddah, Zaky; Sumaryati, Anna; Prawitasari, Dian (Journal of Ecohumanism, 2024)
This study aims to prove that national culture strengthens corporate governance’s impact on integrated reporting. Secondary data are used in this investigation obtained from the integrated reporting database example. The sample was taken using the purposive sampling method which ultimately obtained 336 samples of data, with observation years from 2019-2022. Data processing using Warp PLS version 7.0. This research demonstrates that national culture strengthens corporate governance’s impact on integrated reporting. However, only the culture of uncertainty avoidance and long-term oriented culture have a role in strengthening corporate governance’s impact on integrated reporting. In addition, corporate governance also has a positive effect on integrated reporting. The implication of this study is the importance of the role of national culture and corporate governance on integrated reporting. The originality of this study is that national culture is used to strengthen corporate governance’s impact on integrated reporting, which has so far been difficult to find similar research.